Targeting PAK1 is effective against cutaneous squamous cell carcinoma in a syngenic mouse model - Okumura, Kazuhiro; Morinaga, Takao; Saito, Megumi; Tokunaga, Yurika; Otoyama, Keisuke; Tanaka, Sora; Isogai, Eriko; Kawazu, Masahito; Togashi, Yosuke; Hasegawa, Yoshinori; Wakabayashi, Yuichi (Cancer Science, 2024)
By taking advantage of forward genetic analysis in mice, we have demonstrated that Pak1 plays a crucial role during DMBA/TPA skin carcinogenesis. Although Pak1 has been considered to promote cancer development, its overall function remains poorly understood. To clarify the functional significance of Pak1 in detail, we sought to evaluate the possible effect of an allosteric inhibitor against PAK1 (NVS‐PAK1‐1) on a syngeneic mouse model. To this end, we established two cell lines, 9AS1 and 19AS1, derived from DMBA/TPA‐induced squamous cell carcinoma (SCC) that engrafted in FVB mice. Based on our present results, NVS‐PAK1‐1 treatment significantly inhibited the growth of tumors derived from 9AS1 and 19AS1 cells in vitro and in vivo. RNA‐sequencing analysis on the engrafted tumors indicates that NVS‐PAK1‐1 markedly potentiates the epidermal cell differentiation and enhances the immune response in the engrafted tumors. Consistent with these observations, we found an expansion of Pan‐keratin‐positive regions and potentially elevated infiltration of CD8‐positive immune cells in NVS‐PAK1‐1‐treated tumors as examined by immunohistochemical analyses. Together, our present findings strongly suggest that PAK1 is tightly linked to the development of SCC, and that its inhibition is a promising therapeutic strategy against SCC. PAK1 inhibitor treatment significantly inhibited the growth of tumors derived from 9AS1 and 19AS1 cells in vitro and in vivo.